ANALISIS BIBLIOMETRIK PUBLIKASI PERKEMBANGAN PENELITIAN PEMASARAN DIGITAL KOSMETIK HALAL - Rima Fiandari, Yulist (BACA: Jurnal Dokumentasi dan Informasi, 2022)
Digital marketing development becomes the achievement focus of one government program. The government declares the target as a digital economy country in Asia region. Industry advancement correlates to the research activity conducted by academics. There are two types of cosmetics distributed to the market, namely halal cosmetics and non-halal cosmetics. The objectives of this research were to find out (1) the growth of the numbers of research article and citation, (2) the development article and citation level’s progress, (3) the correlation among the authors (co-authors), (4) the co-occurrence of halal cosmetics-related research in digital marketing from 2016 to 2021. This study was conducted by employing bibliometric method. The data collection applied Publish or Perish method using the key words of “Halal Cosmetics” and “Digital Marketing”. The analysis was done to 60 relevant articles throughout 2016 to 2021. The collected data were analyzed using VOSviewer software. The analysis result showed that the growth of the numbers of article publication and citation level tended to increase per year. The publication achievement in 2016 showed that there were two articles with 7 citations. The articles number published in 2021 increased by 45% and there were 27 articles. Article development showed that the article entitled “Determinants of purchase intention of halal cosmetic products among Generation Y consumers” had 19 citations achievement. Co-author analysis suggested that there were 3 clusters formed. The limited number of formed co-author showed the gap of research development on halal cosmetics in digital marketing. Co-occurrence analysis indicated that there were 8 clusters with halal cosmetics’ purchase decision as the most dominant topic.